Gastroprotective Effect of Galangal, Turmeric and Their Combination on Rats’ Gastric Ulcers - Ekowati, Heny; Anwar, Amalia Meisya; Audina, Fuzilestari Nur; Utami, Esti Dyah (Indonesian Journal of Pharmaceutical Science and Technology, 2025)
Galangal (AG) and turmeric (CL) have potential gastroprotective activity. Both have been shown to prevent oxidation by scavenging free radicals and blocking oxidative enzymes. This study evaluated the gastroprotective effects of galangal, turmeric, and their combination extract against gastric mucosal lesions induced by ethanol-hydrochloric acid (HCl). The experimental design comprised 5 groups: group I was administered with Tween 80 (1%), and group II was administered ranitidine (50 mg/kgBW) orally. The other three groups were administered AG and CL, and their combination was administered (1:1) (100 mg/200 kg BW) orally for six days. On the 7th day, the rats were induced by ethanol-HCl (1: 1 v/v) 8 mL/KgBW. Six hours later, the rat was sacrificed and dissected for their gastric. Gross ulcer area, lesion length, histology, pH, and ulcer index were observed. There were improvements in pH, lesion score, ulcer index, and curative ratio. The histopathological profile showed ulcer repairment and lowering of neutrophil inflammatory cell infiltration. Statistical analysis showed the potential equivalence of the single and combination treatments in their gastroprotective effects. Galangal, turmeric, and its combination have gastroprotective activities by repair of ulcer and gastric pH, increasing the curative ratio, and decreasing the ulcer index in the rat model.